2017
DOI: 10.1080/13697137.2017.1316255
|View full text |Cite
|
Sign up to set email alerts
|

Primary ovarian insufficiency with t(5;13): a case report and literature review on disrupted genes

Abstract: Autosomal translocations are rare in women with POI. We have reported the first case of a de novo reciprocal translocation involving chromosomes 5 and 13 in a POI patient. As one of the breakpoints encompasses the FOXO1 gene, it seems that disruption of this gene can be the cause of POI in this patient. This provides further evidence on the role of autosomal translocations in disrupting POI-associated genes. Therefore, concentrating on the genes at the breakpoints will be helpful to delineate the new biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Primary ovarian insufficiency was found in 1% of Caucasian, 1.4% of Hispanic, 1.4% of African American, 0.5% of Chinese, and 0.1 % of Japanese women (2). Although most commonly deemed as idiopathic, specific etiologies of spontaneous POI include genetic abnormalities, autoimmune conditions, and infections (1,3). Genetic etiologies of POI are most commonly due to abnormalities involving the X chromosome and rarely are associated with autosomal mutations (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary ovarian insufficiency was found in 1% of Caucasian, 1.4% of Hispanic, 1.4% of African American, 0.5% of Chinese, and 0.1 % of Japanese women (2). Although most commonly deemed as idiopathic, specific etiologies of spontaneous POI include genetic abnormalities, autoimmune conditions, and infections (1,3). Genetic etiologies of POI are most commonly due to abnormalities involving the X chromosome and rarely are associated with autosomal mutations (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although most commonly deemed as idiopathic, specific etiologies of spontaneous POI include genetic abnormalities, autoimmune conditions, and infections ( 1 , 3 ). Genetic etiologies of POI are most commonly due to abnormalities involving the X chromosome and rarely are associated with autosomal mutations ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…POI etiology is not well understood [9], but the condition has been widely reported in association with (1) low initial number of follicles, (2) accelerated follicular atresia, (3) compromised maturation process, or (4) folliculogenesis blockage previous to antral stage and ovulation inhibition [10,11]. Reports have suggested that such mechanisms can be activated by iatrogenic, metabolic, infectious, chromosomal, autoimmune, environmental, or genetic factors [12,13].…”
Section: Introductionmentioning
confidence: 99%